Ulipristal Acetate in Myomectomy Optimization in an Infertile Patient with Giant Myomas - Elena de la Fuente; María Dolores Borrás; Miriam Rubio; Nuria Abril (Case Reports in Medicine)
The use of ulipristal acetate (UPA) has been recently introduced in the treatment of uterine leiomyomas. This drug has proven useful to control menometrorrhagia and to reduce myoma size. In the case presented here, we show the benefits of UPA treatment in facilitating surgical removal of giant myomas in an infertile patient. In addition to myoma reduction and a better control of preoperative bleeding, the treatment with UPA reduced the duration and complexity of the surgery, as well as the area of uterine wall involved and the resulting scar. No side effects were observed and the patient became pregnant 6 months after the surgery and had a normal pregnancy and delivery. This case report shows the beneficial effects of UPA in the preoperative treatment of myomas which affect uterus function.